Formulasi dan Uji Aktivitas Antioksidan Kombinasi Bunga Rosella Ungu (Hibiscus sabdariffa L.) sebagai Nutrasetikal - Intan Permata Sari; Yuslia Noviani; Ridwan Rachmadi; Esti Mumpuni (Fakultas Farmasi Universitas Pancasila, 2023)
A nutraceutical is a functional food containing natural components that have the potential for health, especially from medicinal plants. The purple rosela (Hibiscus sabdariffa L.), one of many therapeutic plants that have been effectively transformed into herbal products, is one such example. High quantities of anthocyanin are found in bioactive substances found in rosela flowers. This study aims to formulate and determine the antioxidant activity of purple rosela flower in combination with red ginger and cinnamon bark. Following the liking test, which includes the organoleptic test, and the calculation of shelf life with the Accelerated Shelf-Life Testing (ASLT) method, the brewed tea formulation was kept to determine the total content of phenolate. Antioxidant activity was measured by the DPPH (1,1-diphenyl-2-picrylhidrazyl) method. This study obtained an average result of 0,38±0,05% for the total phenol content of the three formulas. Formula I, II, and III showed antioxidant activity with IC50 values of 21.59 g/mL, 27.13 g/mL, and 20.05 g/mL, respectively. Organoleptic observations that have been observed for 20 days at three different temperatures (4°C, 25°C, and 37°C) in the three formulas indicate no change in color, aroma, or taste, indicating the product remains stable. Based on the score results, the most preferred by panelists was Formula I, with its composition of purple, rose and red ginger.